2018
DOI: 10.1108/apjml-12-2016-0248
|View full text |Cite
|
Sign up to set email alerts
|

Customer’s patronage decision toward health insurance products

Abstract: Purpose The purpose of this paper is to examine the influence of service quality, customer’s satisfaction and religiosity on customer’s patronage decision toward health insurance products. The paper also assesses the influence of religiosity on customer’s patronage decision. The influence of customers’ satisfaction as mediation between service quality and customer’s patronage decision was also measured. Design/methodology/approach A structured questionnaire was developed and administered to a sample of 200 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 124 publications
(103 reference statements)
1
8
0
3
Order By: Relevance
“…Religion is an important predictor of fundamental values. Prior research has shown that religion can strongly influence core value development and hinders the use of unethical products (Quoquab et al , 2017), and consumer motivation to purchase ethically which, in turn, shapes consumption behaviour (Rahman et al , 2018; Minton and Kahle 2013). So, various sellers recurrently use belief cues as marketing tactics to certify positive consumer attitudes by developing consumer trust in their products and services.…”
Section: Mediating Role Of Trustmentioning
confidence: 99%
“…Religion is an important predictor of fundamental values. Prior research has shown that religion can strongly influence core value development and hinders the use of unethical products (Quoquab et al , 2017), and consumer motivation to purchase ethically which, in turn, shapes consumption behaviour (Rahman et al , 2018; Minton and Kahle 2013). So, various sellers recurrently use belief cues as marketing tactics to certify positive consumer attitudes by developing consumer trust in their products and services.…”
Section: Mediating Role Of Trustmentioning
confidence: 99%
“…Providing a diverse range of banking products and services with a more varied financial scheme makes Sharia banking become an alternative for a credible banking system that can be enjoyed by all Indonesians without exception. Based on demands of high service quality performance, customers have high expectations to service quality performance (Rahman et al, 2018). There is still a gap between service performances received with services expected by customer.…”
Section: Introductionmentioning
confidence: 99%
“…The SERVQUAL has shown its efficacy in evaluating consumers' genuine impressions of SQ in a variety of domains, including hospitals, hotels, educational institutions, retail stores, and insurance providers (Alharbi, 2017;Ali et al, 2018;Shafiq et al, 2019;Sharma, 2015). It has also been utilized, tested, and developed in the health-insurance sector (Abu-Salim et al, 2017;Rahman et al, 2018). Thus, its adoption in the present study is justified.…”
Section: Theoretical Background 21 Service Quality (Sq)mentioning
confidence: 96%
“…It has also been utilized, tested, and developed in the health-insurance sector (Abu-Salim et al. , 2017; Rahman et al. , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%